Projeto de letramento na sala de aula: uma experiência com leitura de gêneros textuais - Silva, Elaine Cristine Fernandes da (2015)
This study was part of the reading line of research, writing and Portuguese Language Teaching, the Portuguese Language Program at the Pontifícia Universidade Católica de São Paulo, with a focus on reading focused on the development of a literacy project through genres textual. The overall objective is to contribute to the expansion of the learner's knowledge to act and interact critically in specific contexts. The specific objectives are: 1) to see how our work as teaching being can contribute to the reader and critical training of students through proposals for literacy projects; 2) to propose educational activities for the learner, contact the textual genres, can handle the language in its various contexts in order to act and interact with real communication practices. This research is justified because our practice of classroom has shown us that learners of high school have difficulties to read, understand genres and participate competently in various social practices. Having the hypothesis that the practices of reading and literacy through genres, may contribute to the formation of critical learner we had as a reference for Solé reading approach (2007 [1998]), Smith (2000), Kleiman (1998, 2000, 2004 and 2013), Zanotto (1984), Moita Lopes (1996 and 2002), Bakhtin (2000), Koch (2002), Koch and Elias (2011). For the learner, contact genres, can handle the language in its various contexts in order to act and interact with real communication practices, we made use of the assumptions of genres of Marcuschi (2007 and 2008), Santos (2006 ), Antunes (2002) and the work of Dolz & Scheneuwly (2004 and 2010). With regard to new technologies and genres multisemiotic, consider the ideas of Santos (2002), Rojo (2012), Coscarelli (1999) and Bezerra (2008). This paper is a case study, based on observation and description of a phenomenon in specific context, as Flick (2004), Silva and Menezes (2001), Lüdke & Andrew (2001), Chizzotti (2005), Appolinário (2004) , Triviños (1987) and Andrew (2005). The results showed that the literacy project, based on the genres, contributes to the formation of competent and critical reader, allowing the learner to act in different social demands